Ovens, Peter et al (2012) Developing inquiry for learningRoutledge (New York & London) isbn 978‐0‐415‐59877‐4 226 pp £24.99 http://www.routledge.com/books/details/9780415598774. (19th February 2013) - Smyth, Robyn
Summary The authors provide some useful ideas and a bridge from face‐to‐face into blended learning contexts which teachers interested in an inquiry pedagogy may find useful. There are various scaffolds and exemplars as well as exploration of appropriate digital tools which can be used for critical inquiry. If the content of this book is likely to be relevant to you, I advise that you will probably find only parts of it of interest or use. Robyn Smyth